Polycaprolactone/polysialic acid hybrid, multifunctional nanofiber scaffolds for treatment of spinal cord injury. (1st September 2018) - Zhang, Shuo; Wang, Xiao-Juan; Li, Wei-Shuo; Xu, Xiao-Ling; Hu, Jing-Bo; Kang, Xu-Qi; Qi, Jing; Ying, Xiao-Ying; You, Jian; Du, Yong-Zhong
Graphical abstract: Abstract: Scaffold-based tissue engineering is widely used for spinal cord injury (SCI) treatment by creating supporting and guiding neuronal tissue regeneration. However, how to enhance the axonal regeneration capacity following SCI still remains a challenge. Polysialic acid (PSA), a natural, biodegradable polysaccharide, has been increasingly explored for controlling central nervous system (CNS) development by regulating cell adhesive properties and promoting axonal growth. Here, a polycaprolactone (PCL)/PSA hybrid nanofiber scaffold encapsulating glucocorticoid methylprednisolone (MP) is developed for SCI treatment. Rat models with spinal cord transection is established and the PCL/PSA/MP scaffold is transplanted into lesion area. PCL/PSA/MP scaffold decreases tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) release by inhibiting ionized calcium-binding adapter molecule 1 (Iba1) positive microglia/macrophage activation and reduces apoptosis-associated Caspase-3 protein expression. In addition, the PCL/PSA/MP scaffold inhibits axonal demyelination and glial fibrillary acidic protein (GFAP) expression, increases neurofilament 200 (NF-200) expression and improves functional outcome by Basso, Beattie and Bresnahan (BBB) test. These results demonstrate the therapeutic potential of PSA hybrid nanofiber scaffold in promoting axonal growth and enhancing the functional recovery following SCI. Statement of Significance: Scaffold-based tissue engineering is widely used for spinal cord injury (SCI) treatment by creating supporting and guiding neuronal tissue regeneration. And how to enhance the axonal regeneration capacity following SCI still remains a challenge. Polysialic acid (PSA), a natural, biodegradable polysaccharide, has been increasingly explored for controlling central nervous system (CNS) development by regulating cell adhesive properties and promoting axonal growth. However, in vivo therapeutic effect of PSA scaffolds towards SCI is still lack of evidence and needs to be further explored. In this study, a novel electrospun polycaprolactone/PSA scaffold loaded with methylprednisolone (MP) was developed to achieve efficient therapeutic effects towards SCI. And we believe that it broadens the application of PSA for SCI treatment.